Characterization of Environmental Noise Pollution Based on Noise Measurement and Mapping at USM Engineering Campus. Issue 1 (September 2020) - Khasawneh, O F S; Halim, H; Abdullah, S N; Razali, S A; Algburi, H R F; Salleh, A H
Abstract: This paper describes an analysis of visualizing noise impact on the environment by producing the noise mapping, determining the noise sources and characterization of sound levels measurements at USM Engineering Campus, Nibong Tebal, Penang. Measurements were taken at a total of 30 points with the duration of 3 minutes during working hours using the sound level meter. The ArcMap 10.3.1 software and Google Maps were used to create the noise mapping based on the coordinates and each sampling point. The results revealed that 23 points exceeded the maximum permissible limit, 55 dB(A). The maximum measured sound level was obtained at point 4 (68.3 dB(A)), while the lowest sound level was 43.8 dB(A) at point 26. Characterization of sound levels by measuring the noise levels and performing noise mapping is substantial to analyse and determine the level of noise pollution in institutional and educational areas. In addition, such practices would help in understanding the activities that contribute to the increase in sound level.